PERANAN LEMBAGA PEMBERDAYAAN MASYARAKAT KELURAHAN (LPMK) DALAM MENINGKATKAN PARTISIPASI MASYARAKAT PADA PEMBANGUNAN DI KELURAHAN MAMASA - Damaiwana Damaiwana; Ahmad Saleh (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2020)
The purpose of this study was to identify and describe the role of the Village Community Empowerment Institution (LPMK) in accommodating and channeling community aspirations in the development of Mamasa Village, Mamasa Regency. The method to be used is qualitative research with descriptive research type. The results showed that the role of LPMK in accommodating and channeling community aspirations was still not optimal. LPMK did not schedule the right time to hold a meeting with each head of the ward, so the aspirations by each head of the ward were not effective.